Interplay of Opposing Effects of the WNT/β-Catenin Pathway and PPARγ and Implications for SARS-CoV2 Treatment - Vallée, Alexandre; Lecarpentier, Yves; Vallée, Jean-Noël (Frontiers in Immunology, 2021)
The Coronavirus disease 2019 (COVID-19), caused by the novel coronavirus SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2), has quickly reached pandemic proportions. Cytokine profiles observed in COVID-19 patients have revealed increased levels of IL-1β, IL-2, IL-6, and TNF-α and increased NF-κB pathway activity. Recent evidence has shown that the upregulation of the WNT/β-catenin pathway is associated with inflammation, resulting in a cytokine storm in ARDS (acute respire distress syndrome) and especially in COVID-19 patients. Several studies have shown that the WNT/β-catenin pathway interacts with PPARγ in an opposing interplay in numerous diseases. Furthermore, recent studies have highlighted the interesting role of PPARγ agonists as modulators of inflammatory and immunomodulatory drugs through the targeting of the cytokine storm in COVID-19 patients. SARS-CoV2 infection presents a decrease in the angiotensin-converting enzyme 2 (ACE2) associated with the upregulation of the WNT/β-catenin pathway. SARS-Cov2 may invade human organs besides the lungs through the expression of ACE2. Evidence has highlighted the fact that PPARγ agonists can increase ACE2 expression, suggesting a possible role for PPARγ agonists in the treatment of COVID-19. This review therefore focuses on the opposing interplay between the canonical WNT/β-catenin pathway and PPARγ in SARS-CoV2 infection and the potential beneficial role of PPARγ agonists in this context.